Kontribusi Exercise Identity Terhadap Self-Control dan Cognitive Flexibility pada Mahasiswa Olahraga - Jennifer Novia Rahmawati; Septian Williyanto; Finaldhi Palgunadhi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The present study aimed to investigate the association between exercise identity, self-control, and cognitive flexibility, while also evaluating the predictive role of exercise identity on both psychological outcomes among sport students. A quantitative non-experimental study with a correlational design was conducted involving 124 sport students selected through purposive sampling. Participants met the inclusion criteria of being actively engaged in structured sports activities at least two to three times per week. Data were collected using three standardized instruments: the Exercise Identity Scale (EIS), the Brief Self-Control Scale (BSCS), and the Cognitive Flexibility Inventory (CFI), all of which have demonstrated satisfactory validity and reliability in previous studies. The data were analyzed using descriptive statistics, normality testing, Spearman correlation analysis, and simple linear regression. The results revealed that exercise identity was positively and significantly associated with both self-control (ρ = 0.311, p < .001) and cognitive flexibility (ρ = 0.408, p < .001). Regression analysis further showed that exercise identity explained 14.4% of the variance in self-control (R² = .144, p < .001) and 12.2% of the variance in cognitive flexibility (R² = .122, p < .001). Overall, the findings suggest that students with a stronger exercise identity tend to exhibit higher levels of self-control and cognitive flexibility. However, these psychological outcomes are also likely to be influenced by other factors beyond the scope of the present study. Therefore, future research is encouraged to incorporate additional psychological and contextual variables to achieve a more comprehensive understanding of the factors associated with self-control and cognitive flexibility among sport students. Keywords: Cognitive Flexibility, Exercise Identity, Sport Psychology, Sports Students